Pengaruh Gaya Kepemimpinan Transformasional dan Sarana Prasarana terhadap Budaya Kerja Guru Sekolah Dasar Gugus 4 Parungsari di Kecamatan Sajira Kabupaten Lebak - Tetei Rostiawati; Amalia Sapriati; Tita Rosita (Universitas Mathla'ul Anwar Banten, 2021)
THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE AND INFRASTRUCTURE ON THE WORK CULTURE OF TEACHERS IN ELEMENTARY SCHOOL OF GROUP 4 PARUNGSARI IN SAJIRA SUB-DISTRICT, LEBAK REGENCY. Work culture in schools is closely related to leadership style and facilities and infrastructure. In this case, the low work culture of elementary school teachers is also commonly found in elementary school teachers in Cluster 4 Parungsari, Sajira District, Lebak Regency. Based on data from the Sajira District education office, it was recorded that 52 teachers or 50% (104 teachers from 12 elementary schools) found a low work culture as indicated by the number of teachers who came late to school, the learning process in the classroom did not match the time allocation, and the teacher's lack of creativity in creating innovative learning. This is quite interesting to be studied and analyzed further. The purpose of this study is to analyze the influence of transformational leadership style and infrastructure on the work culture of teachers. This research is quantitative research with Explanatory Survey method. The sample used was 100 elementary school teachers in the Parungsari Village, Group 4, Sajira District, Lebak Regency. Data was collected using a questionnaire/questionnaire. The research results obtained are: 1) There is an influence of Transformational Leadership Style on Teacher Work Culture; 2) There is an influence of Facilities and Infrastructure on the Teacher's Work Culture; 3) There is an influence of Transformational Leadership Style and Infrastructure on Teacher Work Culture.